The rationale to integrate facilities management into the development process. Issue 4 (15th August 2016) - Tucker, Matthew Paul; Masuri, Mohd Rayme Anang
Abstract : Purpose: The purpose of this paper is to justify the need to integrate Facilities Management (FM) into the development process (DP) and establish a framework that potentially serves as a guide to optimise the value of Facilities Management (FM) in the property development industry. Design/methodology/approach: This study looks at the relevant literature to identify the factors that are hindering FM to effectively integrate in the development process. Subsequently, the authors intend to carry out interviews with various professionals in the property development industry in the UK to identify the best practices. This research uses qualitative and quantitative methods in order to establish an FM-DP integration framework. Findings: The literature suggested that contribution of FM towards the property development industry is unquestionable. Surprisingly, in a real world FM has been given a low priority in the property development industry, resulting in Facilities Managers being inadequately integrated into the development process. There is currently no suitable generic mechanism that is practical in all stages of the development process to guide Facilities Managers and/or other professionals to integrate FM into the development process. Originality/value: This study is to provide evidence that the property development industry needs a framework that potentially serves as a guide to optimise the value of Facilities Management (FM) in the development process.